"I neither sleep well nor drive cautiously": How does sleep quality relate to crash involvement directly and indirectly?. (September 2020) - Shams, Zhaleh; Mehdizadeh, Milad; Khani Sanij, Hamed
Abstract: Introduction: Although it seems that sleep quality can simultaneously associate with both risky driving behaviour and crash involvement, previous studies have only investigated these relationships independently, without considering their interrelationships at the same time. Our contribution to the literature is threefold: (1) we examined simultaneous effects of sleep quality, risky driving behaviour and crash involvement in an integrated structural framework, (2) we estimated indirect effect of sleep quality on crash involvement, in addition to, its direct effect, and (3) we investigated the effects of such predictors on crash involvement among professional truck drivers in a country with a low safety performance; Iran. Methods: A cross-sectional questionnaire survey was conducted in 2018 among 1031 truck drivers in rest stops along main roads of Iran. The 19-item Pittsburgh Sleep Quality Index (PSQI) and the 27-item Driver Behaviour Questionnaire (DBQ) were used to measure sleep quality and risky driving behaviour, respectively. Amos.22.0 software, structural equation modelling (SEM) was used to test the hypothesized model. Results: SEM showed that (1) "subjective sleep quality" and "sleep duration", in addition to their direct effect, exerted an indirect effect on crashes through mediator variables (risky driving behaviours), (2) although "habitual sleep efficiency" and "daytime dysfunction" did not directly influence crashes, they were indirectly associated with crash involvement. The "habitual sleep efficiency" was significantly correlated with the reduction of errors and crashes. Increased "daytime dysfunction" was also indirectly related to the growing number of crashes by amplifying aggressive violations, and (3) "sleep disorders" and "sleep latency" solely had a direct effect on crash involvement. Conclusions: Policymakers could (1) build suitable rest stops to improve sleep quality, (2) control drivers' work hours to increase sleep duration and (3) relieve drivers' occupational pressures to lower the probability of traffic crashes. Highlights: Indirect effects of sleep quality on crash risk were investigated among truck drivers. Risky driving behaviour could act as a mediator variable between sleep quality and traffic crashes. Subjective sleep quality and sleep duration exerted indirect effects as well as direct effects. Habitual sleep efficiency and daytime dysfunction had solely indirect effects. Policymakers could build suitable rest stops and control drivers' work hours.